PENGARUH ESG (ENVIRONMENTAL, SOCIAL, AND GOVERNANCE) DAN KEPUTUSAN KEUANGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Tuti Dharmawati; Juni Gultom; Merita Ayu Indrianti; Yusriyah Atikah Gobel; Suhairin Suhairin (ITB AAS Indonesia Surakarta, 2024)
In an era of rapid global change, modern companies face increasing economic, social and environmental pressures. The concept of Environmental, Social and Governance Integration (ESG) is crucial in managing a company, covering three critical dimensions: Environmental, Social and Governance. This research highlights the impact of ESG on financial decisions and corporate performance. Through multiple linear regression analysis on panel data of manufacturing companies on the Indonesia Stock Exchange for 2020-2022, the results show that ESG has a significant contribution with an R Square value of 0.798. Increasing ESG scores is positively related to financial performance, and corporate decisions also have a significant positive influence. These findings provide valuable guidance for companies in understanding and optimizing ESG factors to enhance long-term resilience and growth. While these findings are relevant, future research could broaden the scope to other industry sectors and involve more in-depth analysis of the mechanisms underlying the relationship of ESG, corporate decisions, and financial performance.